Customer engagement, customer equity, and repurchase intention, among Shopee users - Anita Mawarni; Vidyarini Dwita (Operations Management and Information System Studies, 2023)
This study aims to analyze the influence of Customer Engagement on Repurchase Intentions with Customer Equity as mediation for Shopee users. This type of research is quantitative. The population of this study were all Shopee users in Padang City with a total sample of 160 respondents. This research was analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0 Software. The results of this study indicate that: (1) Customer Engagement has a positive and significant effect on Repurchase Intention, (2) Customer Engagement has a positive and significant effect on Customer Equity, (3) Customer Equity has a positive and significant effect on Repurchase Intention, (4) ) Customer Engagement has a positive and significant effect on Repurchase Intention through Customer Equity as a mediating variable.